Concept, Meaning, Necessity, And Criteria Of The Transition Period (Zien Journal of Social Sciences and Humanities, 2025)
A transitional period is a concept that represents the process of transition of a social system from one stage of development to another, the meaning of which is determined by complex social, cultural, and economic changes. This article analyzes the essence of the transition period in society, its necessity, and main criteria. The transition period is closely related to maintaining social stability, managing the processes of renewal and modernization, as well as the formation of new social roles and regulatory systems. The article indicates the level of social integration, stability and flexibility, the adoption of new political and economic forms, and adaptation to cultural changes as criteria for assessing the transition period. Thus, understanding the transition period in society and preparing for it allows for increasing the effectiveness of social development and minimizing problems